Empirical Analysis of Air Pollution Impacts on Jordan Economy - Al-Kasasbeh, Omar; Alzghoul, Amro; Alhanatleh, Hasan (International Journal of Energy Economics and Policy, 2022)
Pollution and the economy appear to be intertwined throughout human history. Our knowledge of the connection between environmental damage and economic growth is fragmented due to disciplinary biases. Accordingly, the purpose of this research is to gain an understanding of the dynamic relationship that exists between air pollution and the economy of Jordan, as well as to investigate the existence of the Environmental Kuznets Curve (EKC), in order to determine which policy options would be most effective in reducing emissions while still allowing for continued economic growth. This study adopted the Bayer-Hanck Cointegration test and Granger Causality tests to achieve the objectives. Bayer-Hanck cointegration indicate that there exists a long-term relationship between air pollutants and economic growth. Moreover, Granger causality test shows that economic growth has a causal effect on the three air pollutants at a significance level of 0.05. By scholarly contributions to the debate between air pollutants and economic growth, this study aims to fill a gap in the existing literature by investigating the EKC hypothesis and the impacts of air pollution on economic growth in Jordan.